The Role of Artificial Intelligence and Digital Information Systems in Enhancing Organizational Management Performance - M Rasyidin; Asep Abdul Sofyan; Supiyandi Supiyandi; Djamaludin; Zulfikar (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The rapid development of Artificial Intelligence (AI) and Digital Information Systems has significantly influenced organizational management practices in various sectors. This research aims to analyze the role of Artificial Intelligence and Digital Information Systems in enhancing organizational management performance through improvements in operational efficiency, decision-making accuracy, employee productivity, communication effectiveness, and system reliability. The study employed a quantitative descriptive method involving organizational employees, managers, and information system administrators as research subjects. Data were collected through questionnaires, observations, and documentation analysis, then analyzed using descriptive statistical techniques. The findings indicate that the implementation of AI-supported Digital Information Systems improved operational efficiency by 23%, decision-making accuracy by 21%, employee productivity by 22%, communication effectiveness by 22%, and system reliability by 20%. The results demonstrate that AI technologies contribute significantly to automating operational processes, reducing human error, accelerating information processing, and supporting data-driven managerial decisions. In addition, integrated digital systems improved organizational coordination, transparency, and information accessibility. Despite several implementation challenges, such as infrastructure limitations and employee adaptation, organizations that successfully adopted AI technologies experienced measurable improvements in management performance and operational effectiveness. Therefore, Artificial Intelligence and Digital Information Systems can be considered effective technological solutions for supporting organizational competitiveness and sustainability in the digital era.